2010
DOI: 10.1097/aln.0b013e3181ca3196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anesthetic Depth Indexes Based on Thalamocortical Local Field Potentials in Rats

Abstract: The permutation entropy corrected with the classic burst suppression ratio is a promising alternative to other indexes of anesthetic depth. Furthermore, high coherence level of activity exists between the somatosensory cortical and thalamic regions, even at deep isoflurane stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 28 publications
8
67
0
Order By: Relevance
“…During the transition from awake to unresponsive, a clear reduction in functional connectivity between the putamen and a wide range of other cortical and subcortical regions occurred, while the connectivity of the thalamus with these regions was maintained. This preservation of thalamocortical connectivity has recently been observed in animals (Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…During the transition from awake to unresponsive, a clear reduction in functional connectivity between the putamen and a wide range of other cortical and subcortical regions occurred, while the connectivity of the thalamus with these regions was maintained. This preservation of thalamocortical connectivity has recently been observed in animals (Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, the volatile agent isoflurane has also been shown to yield increased thalamocortical coherence (33). Thus, our model may not be limited to propofol and predicts an important role of GABAergic pathways in propagating more general anesthetic-induced rhythms.…”
Section: Discussionmentioning
confidence: 95%
“…In what follows, we give a brief overview of applications of ordinal time series analysis to studies of brain (electrical) activity, namely in epilepsy research [63][64][65][66][67][68][69], in anesthesiology [70][71][72][73][74], and cognitive neuroscience [75,76]. All the studies reviewed below investigated brain electrical activity, recorded with electroencephalographic (EEG) techniques.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Electroencephalogram-based parameters typically aim at reducing the complex observed electroencephalographic pattern to a single value associated with the anesthetic drug effect and clinical patient status, e.g., consciousness and unconsciousness. These issues were examined in various studies [70,[72][73][74]79], which consistently showed that permutation entropy can be used to efficiently discriminate between different levels of consciousness during anesthesia, providing an index of the anesthetic drug effect.…”
Section: Anesthesiamentioning
confidence: 99%